Type B non-Hodgkin lymphoma in a patient with acquired immunodeficiency virus with no detected viral load. Case report - Edwin Marcelo Miranda Solìs; Juan Fernando Orozco Herrera (Medisur)
Acquired immunodeficiency virus infection continues to be a major public health problem not only in Ecuador but also throughout the world. Cancer is a common presentation in people living with this virus and represents the main cause of death in this population in most Latin American countries. For these reasons, we present the case of a 58-year-old patient, diagnosed with acquired immunodeficiency virus in the year 2000, who in the last ten years presented adequate clinical, virological, and pharmacological control. Suddenly and a few months ago, he began with symptoms related to a spinal cord compression syndrome at the lumbar level characterized by pain, functional impotence of the extremities and paresthesias. Complementary studies determined the presence of a mass at the medullary level and imaging studies (PET/CT) revealed a tumor mass at the lumbar level associated with multiple retroperitoneal and inguinal lymph nodes. The histopathological results revealed the presence of non-Hodgkin lymphoma, an AIDS-defining neoplasm, which ultimately resulted in the patient's death. The presence of this type of neoplasia is extremely striking after 20 years after the virus was diagnosed and especially after more than ten years of adequate controls and no detected viral loads, which warranted the publication of this case.